U-recycle: mobile application for recycling activites in UiTM Shah Alam / Siti Alieana Shahda Sheikh Ali - Sheikh Ali, Siti Alieana Shahda (2022)
Recycling activity is important to ensure nature’s sustainability in Malaysia. The problem statement of this project is the increase of trash in Malaysia and university students have a low level of recycling awareness. This project aims to developed a mobile application for recycling activity to help reduce waste and promotes recycling in UiTM Shah Alam. The methodology used is Mobile Software Life Cycle (MSDLC). The objectives of this project are to identify the user requirements for U-Recycle; to design U-Recycle and to; develop and demonstrate U-Recycle. The scope of this project is the students and clubs or associations in UiTM Shah Alam. The mobile application main functions are log in, sign up, edit profile and the main features for clubs or associations are QR code generator and view, add, update and delete recycling activity. Meanwhile, the main features for students are a QR code scanner, get their current location, find nearby recycling centre and add recycling activity to their device calendar. The significance of this project is to encourage more clubs and associations to organise more recycling activities and can gain more income. The System Usability Scale (SUS) is used for the system testing, and the score result is 76 for clubs or associations and 79.8 for students. Add the recycling activity date to the calendar intent automatically and develop U-Recycle for iOS platform for Apple users are among the recommendations of the future work from the mobile app limitations.